The Influence of the School Environment on Character Form Students in PKN Lessons - *Nurlailah Nurlailah; Hen Ardiansyah (Universitas Syiah Kuala, 2022)
This study aims to examine the influence of the school environment on the formation of children's character in citizenship education subjects at SDN N0.14 Pajo. Where the school environment is a place or place for children to be guided in all aspects, morals, knowledge, and skills. These things are seen as very important to be fostered by students in the school environment. This type of research is descriptive qualitative research by selecting class V as a sample and 2 informants who are considered to have knowledge and information about the problems studied, namely the Effect of School Environment on the Character Building of students at SDN N0.14 Pajo. Data collection uses descriptive qualitative research methods in the form of: Observation and Documentation, as well as in-depth interviews with informants. In this study, the researchers got quite good results, where the results showed that the influence of the school environment on the formation of children's character, by interviewing informants who were seen from the aspect of the influence of educators, students, canteens, classrooms and playing fields. Meanwhile, educators and students both have a greater positive influence on their presentation compared to the slightly negative influence that exists on the formation of student character.